2014
DOI: 10.1007/s10067-014-2500-y
|View full text |Cite
|
Sign up to set email alerts
|

Drug-free holiday in patients with rheumatoid arthritis: a qualitative study to explore patients’ opinion

Abstract: Clinical trials have shown that in patients with long-standing low disease activity, tapering and/or stopping antirheumatic medication is a realistic option. The objective of this study is to explore patients' opinion about tapering and discontinuing antirheumatic drugs. This qualitative study is based on interviews with 20 patients with rheumatoid arthritis (RA) about RA treatment and treatment discontinuation through structured interviewing. Interviews were tape-recorded, transcribed verbatim, and screened b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Three qualitative studies into the patient perspective on bDMARD dose reduction were identified [98–100]. These studies all found that dose reduction is associated with both positive and negative perceived aspects for patients.…”
Section: Resultsmentioning
confidence: 99%
“…Three qualitative studies into the patient perspective on bDMARD dose reduction were identified [98–100]. These studies all found that dose reduction is associated with both positive and negative perceived aspects for patients.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, an immediate withdrawal of bDMARDs would be unlikely to gain acceptance due to risk aversion among patients and rheumatologists. Patients with RA have been found to be reluctant to change their treatment (e.g., to try a new drug, modify the dose of an existing treatment, or take a so-called drug holiday) and have expressed fears of losing disease control or experiencing flares and side effects [54].…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, daily practice outside a trial often presents a different situation. It is known that outside a trial patients may be reluctant to treatment adjustments , and the same may be true for rheumatologists.…”
Section: Discussionmentioning
confidence: 99%